Relationship Between Abdominal Muscle Strength, Leg Strength and Soccer Kicking Ability Students - Hasanuddin, M Imran; Badaru, Benny; Bachtiar, Ishak; Rahman, Abdul (Sportify Journal, 2026)
Soccer kicking ability is a fundamental skill that supports passing, shooting, and long-ball execution, yet its performance may depend not only on technical execution but also on specific physical components. This study aimed to examine the relationship between abdominal muscle strength, leg strength, and soccer kicking ability among students of SMA Negeri 10 Makassar. A quantitative approach with a descriptive-correlational design was used. The sample consisted of 60 male students selected through simple random sampling. Abdominal muscle strength was measured using a 30-second sit-up test, leg strength was measured using a leg dynamometer, and soccer kicking ability was assessed based on maximal kicking distance. Data were analyzed using descriptive statistics, normality testing, Pearson correlation, and multiple linear regression with SPSS. The findings showed that abdominal muscle strength was positively and significantly associated with soccer kicking ability (r = .522, p < .001), and leg strength also showed a positive and significant association with soccer kicking ability (r = .586, p < .001). Simultaneously, abdominal muscle strength and leg strength were significantly related to soccer kicking ability (R = .671, R² = .450, p < .001). These findings indicate that both trunk-related and lower-limb strength contribute meaningfully to distance-oriented kicking performance. The study provides practical implications for physical education teachers and coaches by emphasizing the importance of integrating abdominal and leg strength development into soccer skill learning and training programs